Relationship between the 17q21 locus and adult asthma in a Czech population - Hrdličková, Barbara; Izakovičová Hollá, Lydie (Human immunology, 2011)
Several whole-genome association studies have shown a significant link between childhood asthma and the 17q12 chromosome region. We selected tagging single nucleotide polymorphisms (SNPs) in the ORMDL3 gene (17q12) to investigate gene variability in relation to adult allergic asthma and asthma/atopy traits in a Czech Caucasian population of adults. We conducted a case-control association study comprising 668 unrelated subjects (337 asthmatic and 331 control subjects). Four selected SNPs (rs17608925, rs12603332, rs8076131, and rs3169572) were genotyped using the TaqMan SNP Genotyping Assays. The single locus analysis showed only a borderline association between rs3169572 variant and asthma (p = 0.030, p(corr) > 0.05). However, seven different haplotypes were identified; among them, the TTAA haplotype was marginally associated with asthma (p = 0.045, p(corr) > 0.05) and TCAG haplotype was significantly associated with asthma in males (p = 0.009, p(corr) < 0.05, odds ratio = 1.48, 95% confidence interval = 1.10-2.00). In addition, associations between the ORMDL3 genotypes and the total IgE level (p = 0.05, p(corr) > 0.05) and hypersensitivity to the pollen (p = 0.007, p(corr) < 0.05) were established. However, no relationship between ORMDL3 SNPs and the pulmonary functions was found (p > 0.05). These findings suggest that the genetic variability in the 17q21 region may be one of the risk factors also for adult asthma, especially in male individuals.
Keywords: dospělí; lidské chromozomy, pár 17; Genetic Loci; odds ratio; Genotype; Female; Adult; ženské pohlaví; jednonukleotidový polymorfismus; Adolescent; Gene Frequency; lidé; Polymorphism, Single Nucleotide; genotyp; Immunoglobulin E; Hypersensitivity, Immediate; membránové proteiny; genetická predispozice k nemoci; studie případů a kontrol; Linkage Disequilibrium; Asthma; vazebná nerovnováha; Genetic Predisposition to Disease; frekvence genu; Risk Factors; časná přecitlivělost; Male; Case-Control Studies; Haplotypes; Czech Republic; bronchiální astma; rizikové faktory; imunoglobulin E; Membrane Proteins; Česká republika; lidé středního věku; haplotypy; mužské pohlaví; White People; Chromosomes, Human, Pair 17; genetické lokusy; běloši; Middle Aged; mladiství; Odds Ratio; Humans